Convolution Neural Network Based Deep Learning Approach for MRI Based Brain Tumour Image Detection - Arthi, M.; Eswaramurthy, V. P. (Indian Journal of Computer Science, 2024)
These days, searching through the vast amount of MRI (Magnetic Resonance Imaging) images by hand to find brain cancer is a very time-consuming and confusing process. It might influence how easily patients have access to the appropriate amount of care. It can be a prolonged operation because it needs a lot of image datasets. It is difficult to distinguish between the tumor regions because brain cancer cells and normal tissues have similar appearances. Consequently, the need arises for an extremely precise automatic tumor identification method.